The Influence of Brand Image, Price and Packaging Design on thePurchase Decision of Pixy Brand Cosmetics (Study on Users in Bandar Lampung) - Melda Suryani; Mahrinasari MS (Inovbook Publications, 2022)
In the increasingly competitive body care and cosmetic industry, the desire to use cosmetic products has fueled competition. Currently, various types of products are circulating in the market, both those produced domestically and abroad. The diversity of cosmetic products circulating in the market will clearly influence consumer decisions in choosing cosmetic products that are suitable for their skin, and there is no risk or harmful effect on skin health.This increasingly competitive market condition makes producers compete in creating products that are most in demand by consumers and must be more creative in reading market wants and needs.. One of the most popular cosmetic brands based on Top Brand Index data is Pixy.The data used in this study is primary data obtained from the results of respondents' answers which were collected with the help of a questionnaire. The number of samples in this study were 170 respondents. The sampling method used purposive sampling, which is a technique to determine the sample with the appropriate criteria determined by the researcher. The analytical method used in this research is validity test, reliability test, analysis stage using multiple linear regression, hypothesis test, namely t test and hypothesis test, namely F test, with the help of the IBM SPSS 26 application program for windows. The results of this study indicate that the variables of Brand Image, Price and Packaging Design have a positive effect on the Purchase Decision Variable